Painel de controle da evasão escolar: manual do usuário - Ferreira, Júlia Angélica de Oliveira Ataíde (Brasil, 2021)
This material is the resulto of the dissertation “Creation of a control panel for the prevention of school dropout at the Federal Institute of Education, Science and Technology of Amazonas”. It is understood that the problem of dropping out of school generates impacts that are not restricted to students who drop out, since it is a situation that generates negative effects for the entire society. The creation of the control panel shown in this material aimed to provide institutions of Professional and Technological Education (EPT) with an easy-to-handle instrument, the correct use of which generates relevant information for the management of school dropout. It is worth noting that this is a scientific-based technological product, which can be replicated in other contexts related to be field of EPT, since school dropout is a problem for national magnitude which requires a diligente posture from school institutions. This material represents a contribution towards proposing a viable solution, which can support the decision-making processo of EPT institutions in preventing school dropout